SISTEM INFORMASI GEOGRAFIS PEMETAAN MITRA MENGGUNAKAN GOOGLE MAPS API DAN LARAVEL - Herdiesel Santoso; Zilfana Falahi; Ahmad Arif Nurrahman; Harimanto (P3M Institut Teknologi Pagar Alam, 2023)
. PT Mustaka Multi Tehnik is a company engaged in several business units, including in the field of producing mosque domes with several types of domes such as stainless steel, decorative colors, color panels and color enamel. PT Mustaka Multi Tehnik mosque dome products have been used by tens of thousands of mosques and prayer rooms spread throughout Indonesia. Marketing PT Mustaka Multi Tehnik has not been able to see the distribution of partners in the form of a digital visualization map. Therefore, it is necessary to have a system that records data in the form of a digital visualization map to display the potential of partners to facilitate marketing. The geographic information system is built by the Waterfall model System Development Life Cycle (SDLC) development method. Unified Modelling Language (UML) as a tool for documenting and specifying the system. Expected outputs are implemented from the Laravel framework and Google Maps APIs to translate latitude and longitude data into objects. After the system is successfully built, the next stage is to carry out functional testing of the black box method. With this web-based geographic information system, recording partner data and potential partner data can already be done digitally. The system successfully runs functionally for users because of the black box method testing, the test also avoids bugs and errors in the system.